PENGUNGKAPAN INFORMASI HUMAN CAPITAL DAN HARGA SAHAM: STUDI PADA HIGH INTELLECTUAL CAPITAL (IC) INTENSIVE INDUSTRIES DI BURSA EFEK INDONESIA - Rudiawarni, Felizia Arni (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2018)
In the accounting’s world, human capital is a part of an intellectual capital (IC) in a group of intangible assets. Human capital began to be recognized as a key factor of a competitive advantage. Disclosure of information related to human capital also contribute to the reduction of asymmetric information between firms and their investors. This study aims to describe the relationship between human capital information disclosure and stock price. The object of this study are firms in the high Intellectual Capital (IC) intensive industry that disclose information about their human capital. This study finds that the disclosure of human capital has positive effect on stock prices, particularly the disclosure of information regarding the qualifications and competence of human capital. In other words, the information about human capital is value relevant.